Comparison between examination with naked eye, curretage and dermoscopy in determining tumor extension before Mohs micrographic surgery - Ali Asilian; Iman Momeni (Advanced Biomedical Research, 2013)
Mohs micrographic surgery (MMS) is a technique for the treatment of cutaneous malignancies. Subtle determination of tumor margin would end to fewer stages of surgery. Our aim was to compare these three ways for determining tumor extension before initiation of MMS, examination with the naked eye, dermoscopy and curettage. Sixty patients who had basal cell carcinoma (BCC) in head and neck area were randomized in three groups (curettage, dermoscopy and examination with the naked eye). Each group encompassed twenty patients. The total number of resection stages in MMS was recorded for each patient. Demographic data of the patients and the total number of resection stages in MMS were statistically analyzed. Based on analysis of variance (ANOVA) test results, there was no significant difference for total number of stages in statistical point of view between three groups (P value = 0.1). In this research, the Pearson correlation coefficient showed that there is a direct relation between the age and resection stages (r = 0.19, P value = 0.04). The Chi-square test showed no differences between three groups in age, residence and radiotherapy history.